Metabolic Profiling of Children Undergoing Surgery for Congenital Heart Disease. Issue 2 (April 2016) - Correia, Goncalo D. S.; Ng, Keng Wooi; Wijeyesekera, Anisha; Gala-Peralta, Sandra; Williams, Rachel; McCarthy-Morrogh, S.; Jiménez, Beatriz; Inwald, David; Macrae, Duncan; Frost, Gary; Holmes, Elaine; Pathan, Nazima
Abstract : Surv Anesthesiol 2016;60(2):70–71 Approximately a third of children who received a diagnosis of congenital heart disease need surgery during early childhood, but these surgical interventions can themselves disrupt homeostatic pathways, ultimately resulting in adverse clinical consequences, including severe organ failure and secondary morbidity. Recent developments in metabolic profiling techniques have shown promise as a means to improve diagnostic accuracy and patient stratification through the identification of metabolic biomarkers of disease risk, severity, and outcome.